It can be solved using PEMDAS rule of mathematics which is used to simplify a mathematical expression in which more than one operation is used.

While solving numerical expressions, first solve:

1.) P = Parentheses

2.) E = Exponents

3.) M = Multiplication

4.) D = Division

5.) A = Addition

6.) S = Subtraction

Now, come to the given problem,

$\displaystyle 9 - {3}\div{\frac{1}{3}} + 1$

first divide than add and subtract

= $\displaystyle 9 - 9 + 1$

= 1

It is the required solution.

While solving numerical expressions, first solve:

1.) P = Parentheses

2.) E = Exponents

3.) M = Multiplication

4.) D = Division

5.) A = Addition

6.) S = Subtraction

Now, come to the given problem,

$\displaystyle 9 - {3}\div{\frac{1}{3}} + 1$

first divide than add and subtract

= $\displaystyle 9 - 9 + 1$

= 1

It is the required solution.

Last edited by a moderator: